Law on the rights of juveniles in criminal proceedings: international and Vietnamese perspectives - Vu, Thi Thu Quyen (Đại học Quốc Gia Hà Nội, 2020)
Juveniles are a group of people in society, who are, on a daily basis, involved in social relations and legal relations to a certain extent. When entering these relationships, juveniles may intentionally or unintentionally violate general rules of conduct. Therefore, depending on the level and nature of the behaviour, juveniles may be subject to different consideration and treatment. Based on age restrictions, national and international legal documents also limit rights, obligations and responsibilities of juveniles when participating in legal relations. This paper comparatively analyses the provisions on the rights of juveniles in criminal proceedings in international law, the laws of some countries and Vietnamese laws, thereby making recommendations for Vietnam. The author argues that laws on juvenile justice in Vietnam are relatively in compliance with international law and the laws of many countries. However, the author also points out some limitations, and based on that, proposes some solutions to perfect the current legal framework on juvenile justice in Vietnam.